2010
DOI: 10.1111/j.1574-6968.2010.02184.x
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms form exocellular structures, trophosomes, to facilitate biodegradation of oil in aqueous media

Abstract: Cytochemical staining and microscopy were used to study the trophic structures and cellular morphotypes that are produced during the colonization of oil-water interfaces by oil-degrading yeasts and bacteria. Among the microorganisms studied here, the yeasts (Schwanniomyces occidentalis, Torulopsis candida, Candida tropicalis, Candida lipolytica, Candida maltosa, Candida paralipolytica) and two representative bacteria (Rhodococcus sp. and Pseudomonas putida) produced exocellular structures composed of biopolyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…Thus, it appears that the local modification of the cell wall during adaptation to growth on hexadecane results in the replacement of polysaccharides within the 'canals' by substances of a different nature. These are likely proteins, as shown in our earlier studies on the localization of oxidative enzymes (Dmitriev et al , ). A protein nature of 'canals' has also been confirmed here, using pronase treatment of hexadecane‐grown cells, in which both ultrathin sections and surface replicas showed that the substance of the 'canals' had been destroyed by pronase (Figure A, B). Under starvation conditions, the dynamics of quantitative changes in polysaccharides during the course of 'canal' formation was different.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Thus, it appears that the local modification of the cell wall during adaptation to growth on hexadecane results in the replacement of polysaccharides within the 'canals' by substances of a different nature. These are likely proteins, as shown in our earlier studies on the localization of oxidative enzymes (Dmitriev et al , ). A protein nature of 'canals' has also been confirmed here, using pronase treatment of hexadecane‐grown cells, in which both ultrathin sections and surface replicas showed that the substance of the 'canals' had been destroyed by pronase (Figure A, B). Under starvation conditions, the dynamics of quantitative changes in polysaccharides during the course of 'canal' formation was different.…”
Section: Discussionsupporting
confidence: 57%
“…This assumption was supported by our electron‐microscopic data on the localization of the product of a cytochemical reaction to oxidative enzymes in the 'canals'. This allowed us to assert that 'canals' are the sites of primary oxidation of hydrocarbons (Dmitriev et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations